2017
DOI: 10.1021/acs.est.7b02875
|View full text |Cite
|
Sign up to set email alerts
|

Fishmeal Application Induces Antibiotic Resistance Gene Propagation in Mariculture Sediment

Abstract: Antibiotic resistance genes (ARGs) are globally prevalent in mariculture sediment, and their presence is an issue of concern in the context of antibiotic use. Although large amounts of fishmeal have been released into the sediment, the role of fishmeal in ARG dissemination remains unclear. In this study, high-throughput ARG profiles in representative fishmeal products and the impact of fishmeal on the sediment resistome were investigated. A total of 132 unique ARGs and 4 mobile genetic elements (MGEs) were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(37 citation statements)
references
References 79 publications
2
34
0
1
Order By: Relevance
“…We found that both physicochemical composting properties and MGE abundances had equally strong direct positive effects on ARG abundances, while bacterial community diversity or composition had no statistically significant effect (Figure 4). This result is in contrast with a previous finding showing that the bacterial community composition is the main factor driving changes in ARG abundances in a mariculture sediment (Han et al, 2017). However, it is consistent with another study, where environmental factors rather than bacterial community composition were more important in driving changes in ARG abundances during composting (Liao et al, 2018).…”
Section: Tracing Arg and Mge Abundances And Diversity Throughout Compsupporting
confidence: 73%
“…We found that both physicochemical composting properties and MGE abundances had equally strong direct positive effects on ARG abundances, while bacterial community diversity or composition had no statistically significant effect (Figure 4). This result is in contrast with a previous finding showing that the bacterial community composition is the main factor driving changes in ARG abundances in a mariculture sediment (Han et al, 2017). However, it is consistent with another study, where environmental factors rather than bacterial community composition were more important in driving changes in ARG abundances during composting (Liao et al, 2018).…”
Section: Tracing Arg and Mge Abundances And Diversity Throughout Compsupporting
confidence: 73%
“…Piscirickettsia , known as salmon pathogens, can be exposed to high levels of antibiotics when present in salmon farms. Recent work has determined that antibiotic resistance genes found in fish stock pathogens can be traced to fish feed (21). The Piscirickettsia plasmids present in the NCBI plasmid database come from strains isolated from salmon farms in southern Chile across multiple studies by two research groups over several years (22, 23).…”
Section: Discussionmentioning
confidence: 99%
“…This concern is illustrated by the widespread and, in some cases, unrestricted use of prophylactic antibiotics in this industry, with the objective of preventing bacterial infections resulting from sanitary shortcomings in fish rearing. This practice has resulted in the emergence of antibiotic-resistant bacteria in aquaculture environments, the increase of antibiotic resistance in fish pathogens, the transfer of these resistance determinants to bacteria affecting land animals and to human pathogens, and alterations of the bacterial microbiome in both sediments and water column (Han et al, 2017). All of these are serious and undesirable outcomes.…”
Section: Introductionmentioning
confidence: 99%